A escrita em espiral como prática de ensino-aprendizagem de escrita no ensino médio - Gomes, Lívia Letícia Zanier (2018)
This research investigates the learning of text production written in Portuguese, in a regular context of a high school classroom in Uberaba-MG, for a period of an academic year, through the text production process ‘Spiral Writing’. It aims to verify if Spiral Writing allows students to improve their language skills. Spiral Writing is a sequential practice of text production followed by constant feedback (in the individual and collective instances) performed in a hybrid context (face-to-face and virtual) allowing shared work among peers. It is supported by the theoretical-methodological framework of Sociodiscursive Interactionism (SDI). Theoretically, this thesis discusses Spiral Writing and feedback, supported by Marra and Lousada (2017), Hattie and Timperley (2007); it mentions the types of correction in student texts (Ruiz, 1998); it discusses the imbrications among learning, adolescence and motivation by the Future Time Perspective Theory (Nuttin and Lens, 1985); it brings Vygotsky's concepts (1984, 2000) that support the Spiral Writing proposal. We then, present a study on the text production according to ISD in Bronckart (2012); we also characterize the essay as a genre, as well as how to select and model a genre in order to teach it. (Dolz and Schneuwly, 2004). Answering the first research question (what representations in relation to linguistic practice are built by the learners from Spiral Writing?), we observe that in their majority: they were able to develop autonomy in relation to their mistakes, when compared to their previous writings and the work of collective feedback; thus, error reduction; they were able to take turns as a more developed pair, learning writing as a reflexive practice, although some still perceived it as a training for the college entrance. Responding to the second question (To what extent do feedback instances contribute – or not – to writing progression?) we could verify development in students’ language skills (albeit in an unregulated way), and we could notice progress in students’ writing during Spiral Writing. Finally, responding to the third question (What impacts on textual production did the use of Virtual Learning Environment produce in Spiral Writing?), we realized that the VLE served as the environment for the text planning stage, allowed the relay of the peers as more developed ones, and optimized the time allocated to regular Portuguese language classes.